Battery diaphragm and preparation method thereof
By extracting the substrate and applying ceramic slurry, a porous film is formed and dried and shaped, the problems of low preparation efficiency and insufficient adhesion of wet-coated diaphragm are solved, and high-quality diaphragm is effectively prepared and reduced The heat shrinkage rate improves the safety of the battery.
Patent Information
- Application Number
- CN202411313405.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing wet-coated diaphragm preparation process is long and complex, with low preparation efficiency, and the resulting diaphragm has a low adhesion force and a high heat shrinkage rate.
By extracting the substrate, a porous film is formed and a ceramic slurry is coated on the porous film. The water content of the porous film is controlled to be 1% to 5%, and the solid content of the ceramic slurry is 45% to 80%, and then dried Styling, reduces the number of drying and shaping times, improves adhesion and reduces heat shrinkage.
It improves the preparation efficiency and quality of the battery separator, enhances the adhesion of the separator, reduces the heat shrinkage rate, and improves the circulation performance and safety of the battery.
Smart Images

Figure CN119208909A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of diaphragm technology, and in particular, to a battery diaphragm and a preparation method thereof. Background Art
[0002] At present, the basic process of wet-coated lithium battery diaphragms is to produce a wet base film of a certain thickness on a wet production line, then carry out subsequent pulping and coating processes, and finally cut into finished diaphragms of different widths. Specifically, it includes: wet base film production process: feeding, extrusion casting, biaxial stretching, extraction, drying and shaping, winding, and slitting; coated diaphragm production process: pulping, unwinding, preheating, coating, drying, winding, slitting, packaging and shipment.
[0003] However, the current wet-coated diaphragm preparation process is long and complicated to manufacture. The wet-coated diaphragm preparation efficiency is low, and the obtained coated diaphragm has low adhesion and high thermal shrinkage. Summary of the invention
[0004] Based on the above-mentioned deficiencies, the present application provides a battery separator and a preparation method thereof to improve the preparation efficiency and quality of the separator.
[0005] This application is implemented as follows:
[0006] In a first aspect, an example of the present application provides a method for preparing a battery separator, comprising:
[0007] Extraction step: extracting the substrate to obtain a porous membrane;
[0008] Coating step: coating a ceramic slurry on the porous membrane to form a coating membrane;
[0009] Drying and shaping step: drying and shaping the coating film to obtain a battery separator;
[0010] Wherein, in the coating step, the water content of the porous membrane is 1% to 5%, and the solid content of the ceramic slurry is 45% to 80%.
[0011] In the above implementation process, the substrate is extracted to form a porous membrane, and then the ceramic slurry is coated on the extracted porous membrane, and the water content of the porous membrane is 1% to 5%, and the solid content of the ceramic slurry is 45% to 80%, and then the coated film is dried and shaped to obtain a battery separator. The slurry is coated on the extracted porous membrane, and the coated film is dried and shaped after the slurry is coated. The porous membrane and the coating layer can be dried in one drying and shaping process. Compared with the traditional method of coating the ceramic slurry on the surface of the membrane after drying and shaping, the number of drying and shaping can be reduced, and the preparation efficiency of the battery separator can be improved.
[0012] In addition, the moisture content of the porous membrane after extraction is controlled to be 1% to 5% and the solid content of the ceramic slurry is controlled to be 45% to 80%. After subsequent drying and shaping, it can improve the bonding strength between the ceramic coating and the porous membrane in the battery separator while reducing the thermal shrinkage of the battery separator.
[0013] In combination with the first aspect, in an optional implementation, the water content of the porous membrane is 2% to 3%; and the solid content of the ceramic slurry is 50% to 60%.
[0014] In the above implementation process, when the moisture content of the porous membrane obtained after extraction is 2% to 3%, applying a ceramic slurry with a solid content of 50% to 60% to the porous membrane can further improve the adhesion of the battery separator and reduce the thermal shrinkage of the battery separator.
[0015] In combination with the first aspect, in an optional embodiment, the method for regulating the water content of the porous membrane includes: in the extraction step, the temperature of the extraction roller is 25-60°C, the temperature of the extraction heating plate is 50-100°C, the ambient temperature is 20-40°C, and the exhaust power is 20-30Hz.
[0016] In the above implementation process, when the substrate is extracted, the temperature of the extraction roller is adjusted to 25-60°C, the temperature of the extraction heating plate is 50-100°C, the ambient temperature is 20-40°C, and the exhaust power is 20-30Hz. A porous membrane with a moisture content of 1% to 5% can be obtained, so that a ceramic slurry with a solid content of 45% to 80% can be subsequently coated on the porous membrane with a moisture content of 1% to 5%, so as to improve the adhesion of the battery separator and reduce the thermal shrinkage of the battery separator.
[0017] In combination with the first aspect, in an optional embodiment, the method of coating a ceramic slurry on a porous membrane comprises:
[0018] The ceramic slurry is coated on the porous membrane using a gravure roller or a slit coating head at a coating speed of 60-120 m / min.
[0019] Optionally, a ceramic slurry with a solid content of 50% to 60% is coated on the porous membrane by a slit coating method.
[0020] In the above implementation process, the ceramic slurry is applied to the porous membrane by using a gravure roller or a slit coating head at a coating speed of 60-120 m / min, which can improve the coating quality. The ceramic slurry with a solid content of 50% to 60% is applied to the porous membrane by a slit coating method, which can improve the coating quality, improve the bonding force of the subsequently prepared battery separator and reduce the thermal shrinkage of the battery separator.
[0021] In combination with the first aspect, in an optional implementation, the thickness of the porous membrane is 3-30 μm, and the thickness of the ceramic coating applied on the porous membrane is 1-5 μm.
[0022] In combination with the first aspect, in an optional implementation, the ceramic slurry includes: ceramic powder, a solvent and an adhesive.
[0023] In combination with the first aspect, in an optional embodiment, in the drying and shaping step, the coated film is sequentially passed through a preheating section and a shaping section in an oven, the temperature of the preheating section is 80-140°C, and the temperature of the shaping section is 90-150°C.
[0024] In the above implementation process, when the coating film after coating the ceramic slurry is dried and shaped, the coating film is first passed through a preheating section with a temperature of 80-140°C for preheating, and then passed through a shaping section with a temperature of 90-150°C for shaping, which can improve the adhesion of the battery separator and reduce the thermal shrinkage of the battery separator.
[0025] In combination with the first aspect, in an optional embodiment, the preparation method further includes a pretreatment step located before the extraction step, and the pretreatment step includes: melt-extruding the raw materials forming the substrate onto a casting roller to form a casting; and biaxially stretching the casting to obtain the substrate.
[0026] Optionally, the preparation method further includes a post-processing step after the drying and shaping step, and the post-processing step includes: rolling up and slitting the battery separator obtained in the drying and shaping step in sequence.
[0027] In the above implementation process, the raw materials forming the substrate are melt-extruded to form a cast sheet, and then the cast sheet is biaxially stretched to obtain a substrate of a certain thickness and width, so that the substrate can be subsequently extracted, coated, dried, formed, rolled and slit to obtain a battery separator of suitable size.
[0028] In combination with the first aspect, in an optional embodiment, the raw materials include polyolefin and a pore-forming agent; the cooling temperature of the casting roller is 19-30°C, the speed is 4-11 m / min, and the residence time is 10-15 min; the biaxial stretching includes longitudinal stretching and transverse stretching, the longitudinal stretching ratio is 6-12 times, and the transverse stretching ratio is 5-10 times.
[0029] In a second aspect, an example of the present application provides a battery separator prepared according to the preparation method provided in the first aspect.
[0030] The battery separator prepared according to the preparation method provided in the first aspect has higher adhesion and lower thermal shrinkage, and when applied to a battery, can improve the cycle performance and safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0032] Figure 1 A schematic diagram of a battery separator provided for an example of this application;
[0033] Figure 2 Schematic diagram of the preparation process of battery separator provided for comparison technology;
[0034] Figure 3 Schematic diagram of the process flow for preparing the battery separator provided for the example of this application.
[0035] Icon: 100 - battery separator; 101 - porous membrane; 102 - ceramic coating. DETAILED DESCRIPTION
[0036] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0037] In lithium batteries, the main function of the separator is to keep the positive and negative electrodes separated to prevent short circuits while allowing the rapid transfer of ions. It is a more important component of lithium-ion batteries. The performance of the separator will directly affect the characteristics of the battery, such as battery capacity, internal resistance, rate, cycle and self-discharge performance.
[0038] At present, the material of lithium-ion battery separators is usually polyolefin materials, which have poor heat resistance. When the battery temperature continues to rise, the separator will shrink or even melt, and the positive and negative electrodes will come into direct contact to produce an internal short circuit, causing the battery temperature to rise sharply and reach the thermal decomposition temperature of the positive and negative electrode materials, which will cause the battery to smoke, catch fire or even explode.
[0039] To improve the thermal stability of the diaphragm, refer to Figure 1 The method currently used is to coat a ceramic coating 102 composed of ceramic and adhesive on a polyolefin porous membrane 101. Since the ceramic coating 102 has good thermal stability and mechanical properties, the safety performance of the battery is greatly improved.
[0040] Typically, see Figure 2 The preparation process of the battery separator 100 composited with the ceramic coating 102 includes:
[0041] S1. Wet base film production process;
[0042] S2. Coated diaphragm production process.
[0043] Please continue to read Figure 2 , S1, wet base film production process, including:
[0044] S11, feeding; S12, extruding cast sheet; S13, biaxial stretching; S14, extraction; S15, drying and shaping; S16, winding; S17, slitting.
[0045] Please continue to read Figure 2 , S2, coated diaphragm production process, including:
[0046] S21, pulping; S22, unwinding; S23, preheating; S24, coating; S25, drying; S26, winding; S27, slitting; S28, packaging and shipment.
[0047] At present, in the preparation process of the battery separator 100, the porous membrane 101 is first prepared by a wet base membrane production process, and then the ceramic coating 102 is prepared on the porous membrane 101 by a coating membrane production process. The preparation process of the battery separator 100 is complicated, the preparation efficiency is low, and the prepared battery separator 100 has low adhesion and high thermal shrinkage.
[0048] Therefore, the present application further improves the preparation process of the battery separator 100, thereby improving the preparation efficiency and quality of the battery separator to a certain extent. In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application.
[0049] See also Figure 3 The method for preparing the battery separator provided in the example of the present application includes:
[0050] S31, feeding;
[0051] S32, extruding cast sheet;
[0052] S33, biaxial stretch;
[0053] S34, extraction;
[0054] S351, pulping;
[0055] S35, online coating;
[0056] S36, drying and shaping;
[0057] S37, rewinding;
[0058] S38, cutting;
[0059] S39, packaging and shipment.
[0060] In the preparation method provided by the example of the present application, the substrate is extracted to form a porous membrane 101, and then the ceramic slurry is coated online on the extracted porous membrane 101, and the water content of the porous membrane 101 is 1% to 5%, and the solid content of the ceramic slurry is 45% to 80%, and then the coated film is dried and shaped to obtain the battery separator 100. The slurry is coated on the extracted porous membrane 101, and the coated film is dried and shaped after the slurry is coated. The porous membrane 101 and the ceramic coating 102 can be dried in one drying and shaping process. Compared with the traditional method of coating the surface of the membrane obtained after drying and shaping with ceramic slurry, the number of drying and shaping can be reduced, and before coating the ceramic slurry, the porous membrane 101 does not need to be preheated, which can improve the preparation efficiency of the battery separator.
[0061] By controlling the moisture content of the porous membrane 101 to 1% to 5% and the solid content of the ceramic slurry to 45% to 80% after extraction, the bonding force between the ceramic coating 102 and the porous membrane 101 in the battery separator 100 can be improved after subsequent drying and shaping, and the thermal shrinkage rate of the battery separator 100 can be reduced.
[0062] In step S31, the raw materials for forming the substrate are pre-treated according to the formula, transported to the extruder for mixing, and the solid materials are plasticized and melted into a melt with uniform temperature and extruded continuously.
[0063] The present application does not limit the composition of the raw materials. In some possible embodiments, the raw materials may include polyolefin powder and a pore-forming agent.
[0064] Exemplarily, the material of the polyolefin powder may be selected from polyethylene.
[0065] For example, the weight average molecular weight of polyethylene can be 0.5×10 6 ~1.5×10 6 .
[0066] Exemplarily, the pore former may be selected from paraffin wax.
[0067] Furthermore, the present application does not limit the specific ratio of the polyolefin powder and the pore-forming agent in the raw material. In some possible embodiments, the mass ratio of the polyolefin powder and the pore-forming agent in the raw material can be 1:1-10.
[0068] Exemplarily, the mass ratio of the polyolefin powder to the pore former in the raw material can be one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10 or a range between any two of them.
[0069] Further, in some possible embodiments, the extruder may be selected from a twin-screw extruder.
[0070] In some possible embodiments, the rotation speed of the twin screw can be controlled at 50-200 rpm, the melt pump pressure can be controlled at 10-50 bar, the residence time can be 10-20 min, and the extrusion volume can be 50-600 kg / min.
[0071] In step S32, the extruder extrude the molten raw material from the die head to the casting roller, and quenches it to obtain a film-like substrate containing a pore-forming agent.
[0072] Furthermore, the present application does not limit the specific parameters of the casting forming. In some possible embodiments, the cooling temperature of the casting roller after the die head can be 19-30°C, the speed can be 4-11 m / min, and the residence time can be 10-15 min.
[0073] Exemplarily, the cooling temperature of the casting rolls can be in the range of one or any two of 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C.
[0074] Exemplarily, the speed of the chill roll may be one of 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min, 10 m / min or 11 m / min, or a range between any two thereof.
[0075] Exemplarily, the residence time may be in the range of one or any two of 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.
[0076] In step S33, the present application does not limit the specific stretching ratio of the biaxial stretching of the cast sheet obtained in step S32. In some possible embodiments, the cast sheet can be stretched longitudinally and transversely, and the longitudinal stretching ratio can be 6-12 times, and the transverse stretching ratio can be 5-10 times.
[0077] For example, the longitudinal stretching ratio may be 6 times, 7 times, 8 times, 9 times, 10 times, 11 times or 12 times, or a range between any two of them.
[0078] For example, the transverse stretching ratio may be 5 times, 6 times, 7 times, 8 times, 9 times or 10 times, or a range between any two of them.
[0079] In step S34 , the substrate containing the pore-forming agent is transported to an extraction tank, and the pore-forming agent is replaced by an extractant to form a porous structure on the substrate, thereby obtaining a porous membrane 101 .
[0080] The present application does not limit the type of the extractant. In a possible embodiment, the extractant may be selected from dichloromethane.
[0081] The water content of the porous membrane 101 can be tested by weighing.
[0082] The method for testing the water content of the porous membrane 101 includes:
[0083] Take a certain area of the porous membrane 101 that has passed through the extraction tank but has not passed through the drying box at the rear, and weigh the wet membrane weight m1 with an electronic balance with an accuracy of 0.0001g; wipe the moisture on the surface of the porous membrane 101 with paper, weigh it again, and obtain the dry membrane weight m2. The moisture content calculation formula is as follows:
[0084]
[0085] In some possible embodiments, the water content of the porous membrane 101 after extraction may be one of 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, or a range between any two of them.
[0086] Furthermore, the present application does not limit specific extraction parameters. In order to facilitate the adjustment of the water content of the porous membrane 101, in some possible embodiments, the present application example provides a method for regulating the water content of the porous membrane 101, including: in the extraction step, adjusting the temperature of the extraction roller to 25-60°C, adjusting the temperature of the extraction heating plate to 50-100°C, the ambient temperature to 20-40°C, and the exhaust power to 23-30Hz.
[0087] Exemplarily, the temperature of the extraction roller may be in the range of one or any two of 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C.
[0088] For example, the temperature of the extraction heating plate may be in the range of one of 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C., or any two thereof.
[0089] For example, the ambient temperature may be one of 20° C., 25° C., 30° C., 35° C. or 40° C., or a range between any two of the above.
[0090] Exemplarily, the exhaust power can be set to one of 23 Hz, 24 Hz, 25 Hz, 26 Hz, 27 Hz, 28 Hz, 29 Hz or 30 Hz, or a range between any two of them.
[0091] Furthermore, the water content of the porous membrane 101 after extraction can be controlled to be 2% to 3%.
[0092] In step S35 , the ceramic slurry is coated on the porous membrane 101 , and the water content of the porous membrane 101 is 1% to 5%, and the solid content of the ceramic slurry is 45% to 80%.
[0093] In some possible embodiments, the solid content of the ceramic slurry may be 45% to 80%.
[0094] Illustratively, the solid content of the ceramic slurry may be in a range between one or any two of 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.
[0095] Furthermore, in some possible embodiments, the solid content of the ceramic slurry may be 50% to 60%.
[0096] The present application does not limit the components of the ceramic slurry. In some possible embodiments, the ceramic slurry may include ceramic powder, a solvent, and a binder.
[0097] Exemplarily, the ceramic powder may be selected from one of aluminum oxide, zirconium oxide, silicon oxide, magnesium oxide, calcium oxide or boehmite, or a range between any two of them.
[0098] For example, the particle size of the ceramic powder may be 0.3-2 μm.
[0099] Exemplarily, the adhesive may be selected from at least one of polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC) and polyvinylidene fluoride (PVDF).
[0100] For example, the solvent may be selected from water, ethanol, glycerol or other polar organic solvents, or acetone, NMP or other non-polar organic solvents.
[0101] Furthermore, additives such as dispersants, wetting agents or surfactants may be added to the ceramic slurry.
[0102] Furthermore, the present application does not limit the specific coating process. In some possible embodiments, a gravure roller or a slit coating head may be used to coat the ceramic slurry on the porous membrane at a coating speed of 60-120 m / min.
[0103] For example, the coating speed may be in the range of one or any two of 60 m / min, 70 m / min, 80 m / min, 90 m / min, 100 m / min, 110 m / min or 120 m / min.
[0104] Furthermore, when the solid content of the ceramic slurry is 50% to 60%, a slit coating head is used for coating.
[0105] In step S36, the coating film obtained in step S35 is dried and shaped.
[0106] In some possible embodiments, the coating film is sequentially passed through a preheating section and a shaping section in an oven, the temperature of the preheating section is 80-140°C, and the temperature of the shaping section is 90-150°C.
[0107] The coating film is sequentially passed through a preheating section at 80-140° C. for preheating and a shaping section at 90-150° C. for shaping, which can reduce the water content of the battery separator 100 and improve the bonding force of the battery separator 100 .
[0108] For example, the temperature of the preheating section may be in the range of one or any two of 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 140°C.
[0109] For example, the temperature of the heat setting section may be in the range of one or any two of 90° C., 100° C., 110° C., 120° C., 130° C., 140° C. or 150° C.
[0110] In step S37 and step S38, the battery separator 100 is rolled up and cut to obtain a battery separator 100 of a set size. In step S39, the battery separator 100 is packaged for easy shipment.
[0111] Furthermore, the present application example provides a battery separator 100, which is prepared according to the above preparation method.
[0112] The battery separator 100 provided in the example of the present application includes a porous membrane 101 and a ceramic coating 102 coated on the porous membrane 101 .
[0113] In some possible embodiments, the thickness of the porous membrane 101 may be 3 to 30 μm, the thickness of the ceramic coating 102 may be 1 to 5 μm, and the thickness of the battery separator 100 may be 4 to 35 μm.
[0114] In the battery separator 100 provided in the example of the present application, there is a high bonding force between the porous membrane 101 and the ceramic coating 102, and the battery separator 100 has a low thermal shrinkage rate, which can improve the safety and stability of the battery when applied to the battery.
[0115] The battery separator 100 of the present application is further described in detail below in conjunction with embodiments.
[0116] Example 1
[0117] Example 1 provides a battery separator 100, and the preparation method is as follows:
[0118] (1) Feeding step: the raw materials include 20% polyethylene powder and 80% paraffin oil by mass percentage; the raw materials are fed into an extruder for melt extrusion;
[0119] (2) Extrusion casting step: the cooling temperature of the casting roller after the die head is 20° C., the speed is 6 m / min, and the residence time is 10 min;
[0120] (3) Biaxial stretching step: longitudinal stretching ratio is 6 times, and transverse stretching ratio is 5 times;
[0121] (4) Extraction step: the substrate is input into the extraction tank for extraction, part of the paraffin oil in the substrate is removed, pores are formed, and the porous membrane 101 is obtained; during the extraction process, the temperature of the extraction heating plate is 60° C., the roller temperature is 35° C., the ambient temperature is 26° C., the exhaust power is 25 Hz, and the water content of the porous membrane 101 after extraction is controlled to be 2%;
[0122] (5) Coating step: Use a slit coating head to coat the ceramic slurry on the porous membrane 101, so that the ceramic slurry and the water on the surface of the porous membrane 101 are fully mixed. The coating speed is 80 m / min, the coating thickness is 3 μm, and a coating film is obtained. The solid content of the ceramic slurry is 50%. Calculated by weight percentage, the components of the ceramic slurry include: 48% alumina powder, 46.4% water, 4.3% adhesive and 1.3% other additives.
[0123] (6) Drying and shaping step: The coated film is transported to an oven for drying and shaping. The oven process temperature is set to step temperature control, the preheating section temperature is 80°C, and the shaping section temperature is 100°C, to obtain a battery separator 100 with a porous film 101 thickness of 9 μm and a ceramic coating 102 thickness of 3 μm.
[0124] Example 2
[0125] Embodiment 2 provides a battery separator 100. Embodiment 3 differs from Embodiment 1 in that:
[0126] In step (4), the temperature of the extraction heating plate is 60° C., the roller temperature is 34° C., the ambient temperature is 25° C., the exhaust power is 25 Hz, and the water content of the porous membrane 101 after extraction is controlled to be 2.3%;
[0127] In step (5), the coating speed is 78 m / min, the solid content of the ceramic slurry is 55%, and the components of the ceramic slurry include, by weight percentage: 52% alumina powder, 40.5% water, 5.5% adhesive, and 2.0% other additives;
[0128] In step (6), the temperature of the preheating section is 79°C and the temperature of the shaping section is 98°C.
[0129] Example 3
[0130] Embodiment 3 provides a battery separator 100. Embodiment 3 differs from Embodiment 1 in that:
[0131] In step (4), the temperature of the extraction heating plate is 58° C., the roller temperature is 34° C., the ambient temperature is 25° C., the exhaust power is 23 Hz, and the water content of the porous membrane 101 after extraction is controlled to be 2.8%;
[0132] In step (5), the coating speed is 75 m / min, the solid content of the ceramic slurry is 60%, and the components of the ceramic slurry include, by weight percentage: 57% alumina powder, 34.7% water, 6% adhesive, and 2.3% other additives;
[0133] In step (6), the temperature of the preheating section is 78°C and the temperature of the shaping section is 98°C.
[0134] Comparative Example 1
[0135] Comparative Example 1 provides a battery separator 100, and the preparation method is as follows:
[0136] (1) Feeding step: the raw materials include 20% polyethylene powder and 80% paraffin oil by mass percentage; the raw materials are fed into an extruder for melt extrusion;
[0137] (2) Extrusion casting step: the cooling temperature of the casting roller after the die head is 20° C., the speed is 6 m / min, and the residence time is 10 min;
[0138] (3) Biaxial stretching step: longitudinal stretching ratio is 6 times, and transverse stretching ratio is 5 times;
[0139] (4) Extraction step: the substrate is input into the extraction tank for extraction, part of the paraffin oil in the substrate is removed, pores are formed, and the porous membrane 101 is obtained; during the extraction process, the temperature of the extraction heating plate is 60° C., the roller temperature is 35° C., and the ambient temperature is 25° C.;
[0140] (5) Drying and shaping step: The porous membrane 101 is transported to an oven for drying and shaping. The oven process temperature is 100° C., and the membrane is rolled up to obtain a porous membrane 101 with a thickness of 9 μm.
[0141] (6) Unwinding and preheating: The porous membrane 101 is unrolled and preheated; the preheating temperature is 70°C.
[0142] (7) Coating step: using a gravure roller to coat the ceramic slurry on the porous membrane 101, the coating speed is 120 m / min, the coating thickness is 3 μm, and a coating film is obtained; the solid content of the ceramic slurry is 35%, and the components of the ceramic slurry include, by weight percentage: 32% alumina powder, 63.3% water, 3.2% adhesive, and 1.5% other additives.
[0143] (8) Drying and shaping step: The coated film is transported to an oven for drying and shaping. The oven process temperature is set to step temperature control, the preheating section temperature is 60°C, and the shaping section temperature is 65°C, to obtain a battery separator 100 with a porous film 101 thickness of 9 μm and a ceramic coating 102 thickness of 3 μm.
[0144] Comparative Example 2
[0145] Comparative Example 2 provides a battery separator 100, which is different from Example 1 in that:
[0146] In step (4), during the extraction process, the temperature of the extraction heating plate is 62° C., the roller temperature is 30° C., the ambient temperature is 27° C., and the water content of the porous membrane 101 after extraction is controlled to be 1%;
[0147] In step (5), the solid content of the ceramic slurry is 35%. Calculated by weight percentage, the components of the ceramic slurry include: 32% alumina powder, 63.3% water, 3.2% adhesive, and 1.5% other additives.
[0148] Comparative Example 3
[0149] Comparative Example 3 provides a battery separator 100, which is different from Example 1 in that:
[0150] In step (4), during the extraction process, the temperature of the extraction heating plate is 50° C., the roller temperature is 30° C., the ambient temperature is 20° C., and the water content of the porous membrane 101 after extraction is controlled to be greater than 5%;
[0151] In step (5), the solid content of the ceramic slurry is 65%. Calculated by weight percentage, the components of the ceramic slurry include: 62% alumina powder, 29.3% water, 6.4% adhesive, and 2.5% other additives.
[0152] Test Case
[0153] The battery separators 100 provided in Examples 1-3 and Comparative Examples 1-3 were subjected to a heat shrinkage test, a peeling force test, and a moisture content test. The test results are shown in Table 1.
[0154] Among them, the test methods for thermal shrinkage include:
[0155] Five samples with a size of 160 mm × 130 mm were uniformly cut from the film roll in the TD direction, and an area of 100 mm × 100 mm was drawn with a ruler to measure the original length L1.
[0156] Preheat the oven to the set temperature and stabilize it for more than 2 hours. Sandwich the sample film with the lines drawn between two A4 papers, put it into the oven, take it out after the specified time, cool it to room temperature, and measure the longitudinal and transverse mark lengths L2. The heat shrinkage calculation formula is as follows:
[0157]
[0158] Where:
[0159] S——thermal shrinkage, %;
[0160] L1——length before heating, mm;
[0161] L2——Length after heating, mm.
[0162] Take the arithmetic mean of 5 samples.
[0163] Peel force test methods include:
[0164] Use an electronic tensile testing machine to cut the film roll into standard strips with a length of 150 mm and a width of 15 mm. Cut 30 mm of double-sided tape and stick it on a glass slide. Stick the ceramic surface of the strip on the tape, and tear off about 1 cm at one end of the strip. Clamp the glass slide with the upper end of the clamp and clamp the end of the torn strip with the lower end. Select the peeling speed and press the start button to ensure that the effective peeling adhesive surface length is 100 mm for the peeling test and record the peeling curve.
[0165] Take 5 longitudinal and transverse specimens respectively, perform arithmetic averaging after testing, and obtain the peeling force data of the specimen.
[0166] Moisture content testing methods include:
[0167] The Karl Fischer moisture test method is used to test the moisture content of diaphragm products. The specific steps are as follows:
[0168] Weigh the sample and place it in a dry container, then add Karl Fischer reagent to completely cover the sample.
[0169] The sample and Karl Fischer reagent are mixed thoroughly to allow them to react.
[0170] During the reaction, the iodine in the Karl Fischer reagent reacts with the water in the sample, consuming a certain amount of iodine.
[0171] By measuring the change in iodine concentration before and after the reaction, the water content in the sample can be calculated. This method is suitable for determining trace water.
[0172] Take 5 sample strips respectively, perform arithmetic averaging after testing, and obtain the moisture data of the sample.
[0173] Table 1
[0174]
[0175] Result analysis:
[0176] In Table 1, by comparing Examples 1-3 and Comparative Examples 2-3, it can be seen that in Comparative Example 2, the solid content of the ceramic slurry is 35%, which is lower than 45%, and the obtained battery separator 100 has a larger thermal shrinkage rate and a smaller peeling force; in Comparative Example 3, the water content of the porous membrane exceeds 5%, and the obtained battery separator 100 has a smaller peeling force, indicating that according to the preparation method provided in the embodiment of the present application, the ceramic slurry is coated on the extracted porous membrane 101 to form a coating film, and then the coating film is dried and shaped, and the water content of the porous membrane 101 is 1% to 5%, and the solid content of the ceramic slurry is 45% to 80%, which can improve the bonding strength of the battery separator 100 while reducing the thermal shrinkage rate.
[0177] By comparing Examples 1-3 and Comparative Example 1, it can be seen that according to the preparation method provided in the embodiment of the present application, a ceramic slurry is coated on the porous membrane 101 after extraction to form a coating film, and then the coating film is dried and formed. This can not only simplify the preparation process and improve the preparation efficiency, but also improve the bonding strength of the battery separator 100 while reducing its thermal shrinkage rate.
[0178] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a battery separator, characterized in that: include: Extraction step: extracting the substrate to obtain a porous membrane; Coating step: coating the ceramic slurry on the porous membrane to form a coating membrane; Drying and shaping step: drying and shaping the coating film to obtain the battery separator; Wherein, in the coating step, the water content of the porous membrane is 1% to 5%, and the solid content of the ceramic slurry is 45% to 80%.
2. The preparation method according to claim 1, characterized in that: The water content of the porous membrane is 2% to 3%; the solid content of the ceramic slurry is 50% to 60%.
3. The preparation method according to claim 1, characterized in that: The method for regulating the water content of the porous membrane comprises: in the extraction step, the temperature of the extraction roller is 25-60° C., the temperature of the extraction heating plate is 50-100° C., the ambient temperature is 20-40° C., and the exhaust power is 23-30 Hz.
4. The preparation method according to claim 2, characterized in that: The method of coating the ceramic slurry on the porous membrane comprises: Using a gravure roller or a slit coating head, at a coating speed of 60-120 m / min, the ceramic slurry is coated on the porous membrane; Optionally, a slit coating head is used to coat the ceramic slurry having a solid content of 50% to 60% on the porous membrane.
5. The preparation method according to claim 1, characterized in that: The thickness of the porous membrane is 3-30 μm, and the thickness of the ceramic slurry coated on the porous membrane is 1-5 μm.
6. The preparation method according to claim 1, characterized in that: The ceramic slurry comprises: ceramic powder, solvent and adhesive.
7. The preparation method according to claim 1, characterized in that: In the drying and shaping step, the coating film is sequentially passed through a preheating section and a shaping section in an oven, the temperature of the preheating section is 80-140°C, and the temperature of the shaping section is 90-150°C.
8. The preparation method according to claim 1, characterized in that: The preparation method further comprises a pretreatment step before the extraction step, wherein the pretreatment step comprises: melting and extruding the raw material for forming the substrate onto a casting roll to form a casting; biaxially stretching the casting to obtain the substrate; Optionally, the preparation method further comprises a post-processing step after the drying and shaping step, and the post-processing step comprises: rolling up and slitting the battery separator obtained in the drying and shaping step in sequence.
9. The preparation method according to claim 8, characterized in that: The raw materials include polyolefin and pore former; The cooling temperature of the casting roller is 19-30°C, the speed is 4-11m / min, and the residence time is 10-15min; The biaxial stretching includes longitudinal stretching and transverse stretching, the longitudinal stretching ratio is 6-12 times, and the transverse stretching ratio is 5-10 times.
10. A battery separator, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing separation membrane for electrochemical device, and separation membrane for electrochemical device prepared thereby
CN105393383A
Low-efficiency and low-consumption water seal lithium ion battery film extraction process
CN107252572A
Lithium battery diaphragm and preparing method thereof
CN109285981A
Method for reducing extruded mimeograph on surface of lithium ion battery diaphragm
CN116417753A
Solvent extraction device for preparing secondary battery separation membrane
CN117584330A
